5 Worlds: The Cobalt Prince - 2 Book 2, The cobalt prince - Siegel, Mark 1967-; Siegel, Alexis; Boume, Xanthe; Rockefeller, Matt; Sun, Boya (New York Random House, 2018)
Sisters Jessa and Oona and new friend Ram Sam Sam try to stop the Cobalt Price from Toki, who orders a strike on Mon Domani, starting a new worlds war.
Keywords: Heroes -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Imaginary places -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Heroes -- Fiction; Adventure and adventurers -- Fiction; Imaginary places -- Fiction; Friendship -- Fiction; Science fiction; Cartoons and comics; Comics (Graphic works); Action and adventure comics; Science fiction comics